Soft Skill Development in Vocational Schools to Produce Competent Graduates Needed by the Business/Industry World - Rismaja Putra (Budapest International Research and Critics University, 2021)
Companies looking for employees, the most important thing is not hard skills, but soft skills, this is because 80 percent of people are successful because of soft skills. In this case, students from the State Vocational School (SMK) in Banda Aceh need to develop good soft skills since grade X. Special attention and synergy between school principals as leaders, teachers and school officers as teachers and mentors need to be done properly. Implementation in a consistent and integrated manner in a sustainable manner will produce graduates and human resources who are superior and skilled, and graduates who are able to meet the needs of the business world and industry.